Historical Singularity and Alternative Representations of the Hundred Years' War in the Fate/Grand Order Game - Muhammad Rezky Noor Handy; Ahmad Aulia Rahman; Pidi Mohamad Setiadi (Yupa: Historical Studies Journal, 2025)
The growing popularity of video games as a means of historical representation has significantly changed how people understand and experience the past. This study analyzes alternative representations of the Hundred Years' War (1337–1453) in the video game Fate/Grand Order, with a focus on the figure of Joan of Arc and the narrative construction of the concept of "historical singularity." Using a qualitative approach combining historical methods and virtual ethnography, documented historical events are compared with the game's narrative. The results reveal fundamental differences in chronology, characters, and conflict motives, reflecting a reinterpretation of the past from a transhistorical and fictional perspective. While the game offers pedagogical opportunities to spark interest in history, it also poses the risk of misinterpretation if not accompanied by critical historical literacy. It concludes that digital history, as presented in Fate/Grand Order, must be approached with a reflective eye to foster a deeper understanding of the relationship between historical reality and its cultural representation in digital media.